ANALYSIS OF THE INFLUENCE OF OPERATING MEDIA TEMPERATURE ON FUEL CONSUMPTION DURING THE STAGE AFTER STARTING THE ENGINE (Perner's Contacts, 2015)
In Current increase in the automobile traffic results in the global increase in fuel consumption and thus the growing volume of pollutants produced during the combustion. Today’s internal combustion engines are optimized for economical and environmental friendly operation with a steady temperature of all operating media, but the heating process still remains a critical phase. The designers of powertrains should therefore focus on the efforts to make this heating phase as short as possible. The paper deals with the analysis of the influence that the operating media temperature has on the consumption in the heating phase.